Aspects of Justice and Legal Certainty in Collecting Carbon Tax - Eko Priyono (Budapest International Research and Critics University, 2022)
The implementation of a carbon tax within rules number 7 of 2021 about the Harmonization of Tax Regulations is believed to be able to control environmental pollution due to carbon emissions while at the same time increasing state revenue. Purchasing carbon and activities that produce carbon emissions are the main targets. Steam power plants (PLTU) as fossil fuel users, become carbon tax subject in the first phase. Other industries that also using fossil fuels have not been given the same tax burden. On the other hand, the imposition of taxes on the purchase of carbon-containing goods causes the levies to be doubled. Every stage of the purchase, from the miner to the user, is taxed at the same rate because it meets the criteria as a buyer of carbon-containing goods. The end user industry is the most affected. Two tax burdens are borne at once. As a buyer of fossil fuels and also as a carbon emissions producer. This normative juridical analysis-based research reveals that the aspects of justice and legal certainty in the imposition of carbon taxes, have not been fulfilled. The unequal treatment of the imposition of carbon taxes has an impact on the level of taxpayer compliance. The imposition of multiple taxes, has an impact on the increase in the cost of production which in turn has an impact on selling prices to consumers. There is a need for stricter and clearer rules to classify the types of purchases that can be subject to a carbon tax, while avoiding double taxation for the same object.